The concept of syndromic diagnoses of osteoarthritis and back pain as a cause of therapy failure - M. V. Putilina; N. V. Teplova; O. S. Gerasimova (Фармакоэкономика, 2021)
Osteoarthritis is considered a peripheral joint disease and is often ignored when discussing the prevalence and treatment of back pain. Traditionally, clinical guidelines from various countries are devoted to the treatment of nonspecific back pain (lower back pain), although this diagnosis is syndromic and is absent in ICD-10. Therefore, in real clinical practice, such diagnoses as osteochondrosis and dorsopathy simultaneously exist. The treatment strategies for back pain do not take into account chronic inflammation directly related to pro-inflammatory cytokines and oxidative stress, which makes drug therapy ineffective. It is advisable from the first days of therapy to choose parenteral forms from the group of symptomatic slow-acting drugs containing chondroitin sulfate (Chondroguard®), which will accelerate the onset of the analgesic effect and increase the effectiveness of pathogenetic therapy.